Personalised higher education based on microcourses: Possible ways of implementation - L. O. Denishcheva; I. S. Safuanov; Yu. A. Semenyachenko (Образование и наука)
Introduction. Educators all over the world agree that human education at any stage of development should be personalised. In order for the training to be personalised, the knowledge, competencies, behaviuoral models and approaches that need to be learned must be presented to a student in such a way that they have a value sense, are relevant and arouse his/her desire to learn even more.The problem of the study is the lack of sound methods for implementing a personalised approach in higher education. At the same time, it is noted that the learning process based on the introduction of microcourses contains the potential for the implementation of personalisation ideas, since microcourses are aimed at meeting the individual needs of the student.Aim. The present research aims to substantiate the possibilities of personalised learning based on microcourses at universities (master’s level).Methodology and research methods. The methodological framework of the research is the theory of the competence-based approach, the paradigm of personality-oriented learning, as well as scientific work in the field of personalised education.Results. The article presents a model of personalised learning at a university based on the use of microcourses. The principles of its construction are described: the responsibility of the university for the preparation of a graduate; reasonable conservatism; compliance of the initiative topic with the direction of training; systematic and systematic control. The concept of a microcourse of an academic discipline is introduced; examples of students choosing microcourses are given. The model of personalisation of education based on the use of microcourses, in addition to traditional sections, such as planned learning outcomes and a calendar curriculum, also contains new aspects (compared to current models of student learning): diagnostics of student’s capabilities in the implementation of personalisation; training regulations (including personal goals); schemes for the selection of general and additional modules, availability of initiative modules; diagnostics of achievements. The results can be broadcast to various areas of master’s degree programmes.Scientific novelty. The scientific novelty consists in the description of the possibilities of implementing a personalised approach in education based on the use of microcourses in master’s degree programmes.Practical significance. The developed model of personalisation of learning based on microcourses can be applied at all levels in the higher education system for various profiles of preparation. It will be especially significant for the profiles of the educational direction.